Análisis de los costos de producción y comercialización según la NIC 41 de la actividad ganadera. - Luna Jara, Zoila Thalia (My University, 2020)
At present, agricultural accounting is relevant for companies with agriculture and livestock activities, as it allows to know the costs and the optimization of their resources. The present case study has as its main objective the determination of the production costs induced in the production of biological assets according to what is determined in the International Accounting Regulations, specifically IAS 41 that has a direct relationship with the processes of livestock activities (fattening, development and production) to then market their cattle in national markets; its proper application allows the company to know if its activities are generating profits or losses, and in particular the identification of the costs (raw material, labor and exploitation costs) that participate in each process of livestock activities for timely decision making and implementation of strategies that allow the generation of competitive advantages. On the other hand, it helps that the Financial Statements demonstrate the costs incurred and through it estimate the profits to be obtained with subsequent sales, being very important to highlight the use of accounting standards related to the type of livestock production, ensuring that its context can foster as a basis for future similar investigations. For the development of this case, descriptive methodology will be implemented with the support of bibliographic sources and application of a non-structured interview with a livestock entrepreneur; In addition, it is concluded that there is a loss for the company, since its production costs and are reduced are affected.
En la actualidad, la contabilidad agropecuaria es relevante para las empresas con actividades de agricultura y ganadería, pues permite conocer los costos y optimización de sus recursos. El presente caso de estudio tiene como objetivo principal la determinación de los costos de producción inducidos en la producción de activos biológicos de acuerdo a lo determinado en la Normativa Internacional de Contabilidad, concretamente la NIC 41 que tiene relación directa con los procesos de las actividades ganaderas (engorde, desarrollo y producción) para luego comercializar sus vacunos en mercados nacionales; su adecuada aplicación permite que la empresa, puedan conocer si sus actividades les está generando utilidades o pérdidas, y en particular la identificación de los costos (materia prima, mano de obra y costos de explotación) que involucran en cada proceso de las actividades ganaderas para la toma de decisiones oportunas e implementación de estrategias que consientan la generación de ventajas competitivas. Por otra parte, ayuda que los Estados Financieros demuestren los costos incididos y a través de ello estimar las utilidades a obtenerse con las ventas posteriores, siendo muy importante resaltar la utilización de normas contables relacionadas con el tipo de producción ganadera, asegurando que su contexto pueda fomentar de base para las futuras investigaciones similares. Para el desarrollo de este caso se implementó metodología descriptiva con el apoyo de fuentes bibliográficas y aplicación de una entrevista no estructura con un empresario ganadero; además, se concluye que existe pérdida para la empresa pues sus costos de producción y comercialización se encuentran elevados.
Keywords: CONTABILIDAD AGROPECUARIA; ACTIVOS BIOLÓGICOS; COSTOS DE PRODUCCIÓN; COSTO DE COMERCIALIZACIÓN